Development and gastrulation in Hyloxalus vertebralis and Dendrobates auratus (Anura: Dendrobatidae) (Amphibian & Reptile Conservation, 2015)
We document the embryonic development of Hyloxalus vertebralis, a frog species of the Ecuadorian highlands, declared as Critically Endangered by the International Union for the Conservation of Nature (IUCN) due to signiicant declines in its populations. Our work may be of value for conservation and management of this endangered frog, especially as it is being bred in captivity to ensure against extinction. We were able to analyze and compare the development of H. vertebralis with Dendrobates auratus (Dendrobatidae), and other frogs, because of the successful reproduction in captivity of Ecuadorian frogs at the Balsa de los Sapos, Centre of Amphibian Investigation and Conservation (CICA), of the Pontiicia Universidad Católica del Ecuador, in Quito. Embryos were ixed, and the external and internal morphology was described from whole mounts, and serial sections. Cellular morphology was analyzed by staining nuclei. Embryos of H. vertebralis and D. auratus developed from eggs that were 2.6 and 3.5 mm in diameter, respectively. In spite of the large size of their eggs, the morphology of H. vertebralis embryos from cleavage to hatching was similar to the morphology of Epipedobates machalilla (Dendrobatidae) embryos. The comparison of gastrulation morphology was extended to six additional species of Dendrobatidae (E. machalilla, Epipedobates anthonyi, Epipedobates tricolor, H. vertebralis, Ameerega bilinguis, D. auratus), and to Xenopus laevis (Pipidae), and Gastrotheca riobambae (Hemiphractidae). We found that elongation of the notochord occurs after blastopore closure in the six species of dendrobatid frogs, as in G. riobambae; whereas gastrulation and notochord elongation overlap during X. laevis development. We propose that the separation of gastrulation from notochord elongation may relate to slower development patterns, probably associated with the terrestrial reproductive strategies of dendrobatid frogs and marsupial frogs. This analysis contributes to the knowledge of frog embryology and gastrulation, and provides developmental information that may be useful for the conservation and management of H. vertebralis.
Centro Jambatu - ID 1556